Psychometric properties of the Spanish version of the Patient Health Questionnaire in Mexican adolescents - Díaz de León Castañeda, Christian; Díaz-Castro, Lina (Frontiers in Psychology, 2025)
IntroductionThe present study aimed to contribute to the analysis of the psychometric properties of the Patient Health Questionnaire (PHQ-9) in a sample of adolescents residing in San Luis Potosí (SLP), Mexico.Methods768 adolescents from SLP, Mexico, participated in the study. Confirmatory factor analysis (CFA) was conducted to test the one and two-factor models, taking into account the ordinal nature of the items in the model estimation method. Internal consistency was evaluated using the Coefficient alpha (α) and Coefficient omega (ω). Invariance measurement by sex was tested. Also, the relationship with the General Anxiety Disorder (GAD-7 scale) was tested.ResultsThe CFA analyses indicated that both models, the one-factor model and the two-factor model, had a very good fit. The single factor and the two factors of the models demonstrated acceptable internal consistency (Coefficient alpha ranging from 0.779 to 0.896). Both models demonstrated measurement invariance by sex up to the Strong level. Additionally, a high Pearson correlation was found between the PHQ-9 and GAD-7 total scores (r = 0.812).ConclusionIt is concluded that the PHQ-9 scale presents good psychometric properties for the Mexican adolescent population.